Boundaries within: Nation, Kinship and Identity among Migrants and Minorities - Decimo, Francesca; Gribaldo, Alessandra (Springer International Publishing : Imprint: Springer, 2017)
This volume investigates the relationship between migration, identity, kinship and population. It uncovers the institutional practices of categorization as well as the conducts and the ethics adopted by social actors that create divisions between citizens and non-citizens, migrants and their descendants inside national borders. The essays provide multiple empirical analyses that capture the range of politics, debates, regulations, and documents through which the us/them distinction comes to be constructed and reconstructed. At the same time, the authors reveal how this distinction is experienced, reinterpreted, and reproduced by those directly affected by governmental actions. This perspective grants equal attention to both the logics of national governmentality and the myriad ways that individuals and collectivities entangle with categories of identity. Featuring case studies from countries as varied as the Netherlands; French Guiana; South-Tyrol; Eritrea and Ethiopia; New York City; Italy; and Liangshan, China, this book offers unique insights into the production of identity boundaries in the contested terrain of migration and minorities. It outlines how the process of producing national identity is enacted not only through impositions from above, but also when individuals themselves embody and deploy identities and kinship bonds. More so than lines of division, boundaries within are understood as an ongoing process of identity construction and social exclusion taking place among the various actors, levels, and spaces that make up the national fabric. Finely-grained and engaging case studies of collective categorization and the challenge of identity formation taken as a whole convincingly illustrate the utility of the editors' idea of "boundaries within," a concept cogently developed in their framing chapters. Peter Kivisto, Augustana College and St. Petersburg State University Drawing on research in a range of global contexts, the essays in this volume provide fascinating new insights and raise important questions about the intersection of state policies, family and kinship, and the construction of identities among migrants and minorities. Nancy Foner, Distinguished Professor of Sociology, Hunter College and Graduate Center of the City University of New York This excellent collection of ethnographic studies helps to understand how statistical categories and national boundaries constructed by states intersect and interfere with kinship patterns and social identities of migrants and minorities in complex, intrusive and paradoxical ways. Rainer Bauböck, European University Institute, Florence.
Keywords: Social sciences.; Political science.; Ethnicity.; Emigration and immigration.; elektronické knihy; electronic books